Combining C-arm CT with a new remote operated positioning and guidance system for guidance of minimally invasive spine interventions. (5th March 2014) - Czerny, Christoph; Eichler, Katrin; Croissant, Yann; Schulz, Boris; Kronreif, Gernot; Schmidt, Renate; von Roden, Martin; Schomerus, Christof; Vogl, Thomas J; Marzi, Ingo; Zangos, Stephan
Abstract : Objective: To report our experience using C-arm cone beam CT (C-arm CBCT) combined with the new remote operated positioning and guidance system, iSYS1, for needle guidance during spinal interventions. Methods: A C-arm CBCT with a flat panel angiography system was acquired (Artis Zeego; Siemens Healthcare Sector, Forchheim, Germany). Reconstruction of CT-like images and planning of the needle path were performed using a common workstation. The needle holder of iSYS1 acted as a guide during insertion of Kirschner (K) wires. 20 percutaneous K wires were placed in the pedicles at T2–T3, T7–T12, and L1–L2 in a cadaver specimen. Postprocedure C-arm CBCT scans were obtained to confirm the accuracy of the K wire placement. Results: All K wire placements were successfully performed. Mean planning time with Syngo iGuide was 4:16 min, mean positioning time of iSYS1 was 3:35 min, and mean placement time of the K wires was 2:22 min. Mean total intervention time was 10:13 min per pedicle. A mean deviation of 0.35 mm between the planned path and the placed K wire with a mean path length of 6.73 cm was documented. Conclusions: Our results demonstrate the potential of combining C-arm CBCT with iSYS1 for safe and accurate percutaneous placement of pedicle K wires in spinal interventions.